2000
DOI: 10.1074/jbc.m004292200
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activity of a Large Conductance, Calcium-sensitive K+ Channel in the Presence of Src Tyrosine Kinase

Abstract: Large conductance, calcium-sensitive K ؉ channels (BK Ca channels) contribute to the control of membrane potential in a variety of tissues, including smooth muscle, where they act as the target effector for intracellular "calcium sparks" and the endothelium-derived vasodilator nitric oxide. Various signal transduction pathways, including protein phosphorylation can regulate the activity of BK Ca channels, along with many other membrane ion channels. In our study, we have examined the regulation of BK Ca channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 53 publications
8
98
1
1
Order By: Relevance
“…In these assays we stimulated PKA activity intimately associated with the channel by applying cAMP to the intracellular face of isolated inside-out patches. As previously reported (17) the effects of cAMP in this system are dependent upon the presence of Mg-ATP, and the actions of cAMP are completely abolished by the PKA inhibitor peptide PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Although STREX channels are inhibited whereas ZERO channels are activated by PKA closely associated with the channel (17), the short LZ1-competing peptides effectively blocked PKAdependent regulation of either splice variant.…”
Section: Pkac Docking With Mouse Bk Channel Variants Mediated Via a Lz1supporting
confidence: 51%
See 1 more Smart Citation
“…In these assays we stimulated PKA activity intimately associated with the channel by applying cAMP to the intracellular face of isolated inside-out patches. As previously reported (17) the effects of cAMP in this system are dependent upon the presence of Mg-ATP, and the actions of cAMP are completely abolished by the PKA inhibitor peptide PKI [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Although STREX channels are inhibited whereas ZERO channels are activated by PKA closely associated with the channel (17), the short LZ1-competing peptides effectively blocked PKAdependent regulation of either splice variant.…”
Section: Pkac Docking With Mouse Bk Channel Variants Mediated Via a Lz1supporting
confidence: 51%
“…Phenotypic variation in native BK channels results from extensive alternative exon splicing of the ␣-subunit (6, 9, 10) as well as through interaction with regulatory ␤-subunits and accessory proteins (11)(12)(13). The BK channel ␣-subunit is a target for regulation by multiple protein kinases and protein phosphatases (3, 14 -18), and several protein kinases have been reported to co-immunoprecipitate with mammalian BK channels (3,16,17). Although several consensus phosphorylation sites have been identified by mutagenesis within the intracellular C-terminal domain, BK channel ␣-subunits do not contain previously identified protein-protein interaction domains.…”
mentioning
confidence: 99%
“…We have previously shown that activation of VSM ␣5␤1 integrins leads to potentiation of L-type calcium channel current through the involvement of the integrin-associated tyrosine kinases c-src and focal adhesion kinase (13,14). Other studies have reported that BK channel activity is enhanced following direct channel phosphorylation by other src family kinases and by Pyk2 (proline-rich tyrosine kinase 2) (7,8). Recently, we found that the endogenous ␣5␤1 integrin ligand fibronectin (FN) potentiates BK channel current in VSM cells (15).…”
Section: ؉mentioning
confidence: 99%
“…Phosphorylation of the BK channel by tyrosine kinases, including focal adhesion kinase (6) and c-src (7,8), suggests a possible involvement of the channel in integrin signaling. Integrins are a widely expressed class of adhesion receptor whose interactions with extracellular matrix (ECM) proteins lead to activation of signaling cascades, including protein tyrosine phosphorylation (9).…”
Section: ؉mentioning
confidence: 99%
“…In Drosophila, two cytosolic regulatory proteins, Slob and dSLIP, and two protein kinases, Src and PKAc, are able to assemble with the slo ␣-subunit (27)(28)(29). In vertebrates, however, only kinases, such as Src and Syk, have been reported to interact with this subunit (30)(31)(32). To seek other proteins that associate with K Ca channels and mediate their presynaptic targeting, we used yeast two-hybrid screening to search a cDNA library made from sensory epithelia of the chicken's cochlea.…”
mentioning
confidence: 99%